PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS SAINS, LINGKUNGAN, TEKNOLOGI, DAN MASYARAKAT UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI SMA/MA - Jihad, Ruhul; Suma, Ketut; Rahmawati, Dewi Oktofa (Jurnal Pendidikan Fisika Undiksha, 2024)
The results of learning physics for grade XI high school / MA students are still low, one of the reasons is that the teaching materials used are still dense, textual, and the media used is still not attractive. Based on these problems, researchers aim to (1) develop attractive physics e-modules based on science, environment, technology, and society to improve physics learning outcomes of grade XI high school / MA students, (2) describe the practicality of interactive physics e-modules based on science, environment, technology and society, and (3) describe the effectiveness of s-based interactive physics e-modules AINS, environment, technology and society in improving physics learning outcomes of grade XI high school / MA students. The e-module development model uses ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development. The subjects in this study were 2 physics lecturers, 5 practicality teachers, and 32 students of SMA Negeri 2 Banjar. The data analysis technique used is quantitative descriptive. The results of the research obtained (1) the interactive physics e-module is very feasible to be used with an average value of media experts of 0.92 and material experts of 0.96 in the very feasible category, (2) the interactive physics e-module is very practical to use in learning with an average value of teacher practitioners of 93% of the very practical category and student response questionnaires of 75% of the Practical category, and (3) the attractive physics e-module is effective enough to improve student physics learning outcomes with a value obtained of 0.44 medium category. Based on the results of data analysis described above, it can be concluded that SLTM based e-modules are feasible to use, practical, and quite effective in improving the learning outcomes of physics class XI SMA/MA.